Enhancement of spin polarization induced by Coulomb on-site repulsion between localized pz electrons in graphene embedded with line defects. Issue 45 (3rd November 2015) - Ren, Ji-Chang; Wang, Zhigang; Zhang, Rui-Qin; Ding, Zejun; Van Hove, Michel A.
Abstract : The spin polarization distributions of the system are very sensitive to the values of Coulomb on-site repulsion at ELDs, indicating that the Coulomb on-site repulsion cannot be ignored in this system. Abstract : It is well known that the effect of Coulomb on-site repulsion can significantly alter the physical properties of the systems that contain localized d and/or f electrons. However, little attention has been paid to the Coulomb on-site repulsion between localized p electrons. In this study, we demonstrated that Coulomb on-site repulsion between localized p z electrons also plays an important role in graphene embedded with line defects. It is shown that the magnetism of the system largely depends on the choice of the effective Coulomb on-site parameter U eff . U eff at the edges of the defect enhances the exchange splitting, which increases the magnetic moment and stabilizes a ferromagnetic state of the system. In contrast, U eff at the center of the defect weakens the spin polarization of the system. The behavior of the magnetism is explained with the Stoner criterion and the charge accumulation at the edges of the defect. Based on the linear response approach, we estimate reasonable values of U eff to be 2.55 eV (2.3 eV) at the center (edges) of the defects. More importantly, using a DFT+ U + J method, we find that exchange interactions between localized p electrons also play an important role in the spin polarization of the system. These results imply that Coulomb on-site repulsion is necessary to describe the strong interaction between localized p z electrons of carbon related materials.